PENERAPAN PEMUNGUTAN PAJAK HOTEL PADA ONLINE TRAVEL AGENT (Studi Kasus Pada Hotel Selecta Kota Batu Jawa Timur) - Dayinta Sukma Bidari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
As internet marketing-based business, Online Travel Agents (OTA) use websites accessible from any places around the globe as long as the internet is available. The use of OTA helps hotels to market their services to customers and simplify their effort to reach customers at any place and any time. The obstacle for them in their partnership with OTA is the fee or commission that they have to pay, which ranges from 20 to 30 percent for foreign OTA companies. The basis for hotel tax levy is the published price, not the agreed price, so tax basis becomes higher. The higher the hotel rooms’ published price, the higher the tax potentials. The management of Selecta Hotel agreed that hotel tax levy based on OTA has a high tax potential.Keywords: Tax, Hotel Tax, Online Travel Agents